DESIGN OF INFORMATION AND TECHNOLOGY BASED TEACHING MATERIALS IN MATHEMATICS SUBJECTS OF IT HIGH SCHOOL PEKANBARU STUDENTS - Rahmadani, Heni; Roza, Yenita; Murni, Atma (MEJ (Mathematics Education Journal), 2020)
This research is based on the low mathematical representation ability of students and the lack of textbooks used by teachers in presenting teaching material. This study aims to describe the results of the development of information technology-based teaching materials to improve the mathematical representation ability of students in class X Trigonometry Function Materials that are valid, practical, and effective. The model used in this research development is the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The research instruments used in this article are validation sheets (validity aspects), teacher assessment sheets and student assessment sheets (practical aspects), and mathematical representation ability tests (effectiveness aspects). Analysis of the data used in this research is parametric statistics, the t-test with the help of SPSS 18.00 using the Independent-Sample t-Test. This research resulted in a product of teaching materials based on information and technology in valid mathematics (87.11%), practical (90.81%) and effective (0.043 <0.05).